The new know : innovation powered by analytics - May, Thornton A. (Hoboken, N.J. : Wiley, 2009)
"Learn to manage and grow successful analytical teams within your business Examining analytics-one of the hottest business topics today-The new know argues that analytics is needed by all enterprises in order to be successful. Until now, enterprises have been required to know what happened in the past, but in today's environment, your organization is expected to have a good knowledge of what happens next. This innovative book covers Where analytics live in the enterprise The value of analytics Relationships betwixt and between Technologies of analytics Markets and marketers of analytics The new know is a timely, essential resource to staying competitive in your field"--Provided by publisher
The New Know: Innovation Powered by Analytics; Contents; Foreword: The Blending of Insight and Technology; Foreword: Are We at the Advent of Something Big?; Introduction: Standing at a Hinge of History; Chapter 1: The Art, Act, and Science of Knowing; Chapter 2: A Transformed World; Chapter 3: The Analyst: A New Animal in The Organizational Forest; Chapter 4: Where Analysts Live in the Organization; Chapter 5: Relationships Betwixt and Between; Chapter 6: The Evolution of the Technologies of Analytics; Chapter 7: Value of Analytics: Knowledge, Strategy, and Innovation.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Business intelligence; Technological innovations; Innovations; BUSINESS & ECONOMICS -- Information Management; BUSINESS & ECONOMICS -- Knowledge Capital; Business intelligence; Technological innovations; Analyse; Business Intelligence